PERAN PEMBIMBING DAN PENYULUH DALAM PEMBENTUKAN KARAKTER SANTRI BARU PADA MASA PANDEMI COVID 19 (Studi Kasus di Pondok Pesantren Wali Songo Ngabar 2021) - Siti Khusnul Faizah; Arsyad Bayanul Hakim (Taqorrub: Jurnal Bimbingan Konseling dan Dakwah, 2023)
Abstract The creation of quality human development in Indonesia is of course not only in terms of academics, but also based on high moral values. Here the WaliSongoNgabar Islamic Boarding School applies a character guidance system for new students. Even though the Covid-19 pandemic is a challenge for the supervisors, because there are certain restrictions that require more effort in guiding new students. The problem statements are: (1) How is the implementation of guidance and counseling for new students during the Covid 19 pandemic at the WaliSongoNgabar Islamic Boarding School in 2021, (2) How is the character formation of new students during the Covid 19 pandemic at the WaliSongoNgabar Islamic Boarding School 2021, (3) What is the role of mentors and extension workers in shaping the character of new students during the Covid 19 pandemic at the WaliSongoNgabar Islamic Boarding School in 2021 This research uses descriptive qualitative method. With the object of the new santriustadz supervisor and the caretaker as a data source and the new santri dormitory building as the field object, the results of the research are (1) the first implementation of the 2021 new santri guidance is the 2nd year and still has several problems in its implementation, namely about resources. lack of human resources and seniority, (2) The formation of this character is carried out with good habits in daily activities for example clean living habits such as picket every day and community service every Friday. (3) the role of the supervisor and the instructor is divided into 2, namely the curative role, namely the mentor as a person who helps in solving problems and the preventive role, namely the supervisor as the person who prevents problems from occurring for new students.